Improving the Performance Effectiveness of Groups Through a Task-Contingent Selection of Intervention Strategies - Herold, David M. (Academy of Management Review, 1978)
David M. Herold, Improving the Performance Effectiveness of Groups through a Task-Contingent Selection of Intervention Strategies, The Academy of Management Review, Vol. 3, No. 2 (Apr., 1978), pp. 315-325